High rate kinematic GNSS observations for local-tie survey - Kabir, Syed Rezwan (My University, 2011)
Onsala Space Observatory (OSO) is a fundamental geodetic station with co-located geodetic equipment. OSO takes part in the International VLBI Service (IVS) and the International GNSS Service (IGS) by a radome enclosed 20 meter radio telescope and a GNSS-monument and corresponding receiver, respectively. Additionally, a GNSS antenna was mounted on top of the 20 meter radio telescope in late 90’s to determine the Invariant Point (IVP) of the telescope. The International Terrestrial Reference Frame (ITRF) is maintained by using measurements of several space geodetic techniques, VLBI, GNSS, Satellite Laser Ranging (SLR) and Doppler Orbitography and Radiopositioning Integrated by Satellite (DORIS). The global network of geodetic fundamental stations forms the backbone of the ITRF. To maintain the ITRF it is therefore very important to know the relative position of the geodetic equipments at these stations very precisely. In order to measure the local-tie between the 20 meter radio telescope and the GNSS station at OSO several local-tie survey campaigns were performed since the 90’s. But, except the most recent one performed in 2008, these survey campaigns did not provide the complete covariance information of the local-tie. In the 2002 and 2008 local-tie surveys, a hybrid technique was followed to determine the IVP of the 20 meter radio telescope. The problem with this approach is that it is very time consuming and needs various advanced equipment (i.e. laser tracker, reflector, markers, ground pillars). This master's thesis project was therefore to implement a more convenient technique to determine the IVP of the radio telescope at OSO. The indirect approach proposed by Finnish researchers to obtain the reference point of an azimuth-elevation type telescope was modeled and simulated in order to determine the IVP of the radio telescope. High-rate GNSS data observed with the antenna on top of the radio telescope were analyzed with a scientific GNSS processing software package. Both, GNSS-observations acquired during dedicated observing sessions and during standard telescope operation were analyzed with a kinematic approach. The corresponding results for the position of the GNSS-antenna were used to derive the IVP of the radio telescope.
Keywords: Grundläggande vetenskaper; Annan naturvetenskap; Annan teknik; Basic Sciences; Other Natural Sciences; Other Engineering and Technologies